2017
DOI: 10.1038/s41598-017-02383-y
|View full text |Cite
|
Sign up to set email alerts
|

Reef-building corals thrive within hot-acidified and deoxygenated waters

Abstract: Coral reefs are deteriorating under climate change as oceans continue to warm and acidify and thermal anomalies grow in frequency and intensity. In vitro experiments are widely used to forecast reef-building coral health into the future, but often fail to account for the complex ecological and biogeochemical interactions that govern reefs. Consequently, observations from coral communities under naturally occurring extremes have become central for improved predictions of future reef form and function. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
144
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 108 publications
(152 citation statements)
references
References 49 publications
(59 reference statements)
8
144
0
Order By: Relevance
“…Mangrove systems have dynamic temperature, pH and oxygen profiles, and as such, expose resident corals to very different physicochemical conditions than neighboring reefs (Camp et al, 2017). Mangroves are highly heterogeneous in nature, with freshwater input, organic content, system size and consequently water residency time, along with other benthic components (e.g., seagrass composition) influencing the local physicochemical conditions.…”
Section: Mangrove Habitatsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mangrove systems have dynamic temperature, pH and oxygen profiles, and as such, expose resident corals to very different physicochemical conditions than neighboring reefs (Camp et al, 2017). Mangroves are highly heterogeneous in nature, with freshwater input, organic content, system size and consequently water residency time, along with other benthic components (e.g., seagrass composition) influencing the local physicochemical conditions.…”
Section: Mangrove Habitatsmentioning
confidence: 99%
“…For example, work in the Caribbean (Yates et al, 2014) suggested that mangroves could act as a potential refuge for corals, through physical shading and the elevation of downstream A T as a result of carbonate-sediment dissolution (i.e., buffering potential similar to seagrass habitats), as well as frequent exposure to more variable temperatures. In other locations [e.g., the Seychelles, Indonesia (Camp et al, 2016a) and New Caledonia (Camp et al, 2017)] mangrove systems have exposed corals to simultaneously low pH, low oxygen and warmer waters relative to adjacent reefs. As such, these mangrove systems may precondition corals to future climates (Camp et al, 2016a) or house corals more resilient to future climate conditions (Figure 2, Camp et al, 2017).…”
Section: Mangrove Habitatsmentioning
confidence: 99%
See 2 more Smart Citations
“…What environmental conditions are associated with the presence of heat adapted alleles? Certainly, the extreme temperature profiles of the HV pool are not unique to Ofu; corals are found in a variety of extreme environments and are exposed to temperatures that would cause bleaching in their conspecifics from other areas (Coles and Riegl, 2013;Kline et al, 2015;Richards et al, 2015;Camp et al, 2017). Wide variation in thermal tolerance and genetic divergence has been reported across latitudes and at large-spatial scales (Middlebrook et al, 2008;Howells et al, 2013;Dixon et al, 2015;Thomas et al, 2017), and it is becoming increasingly clear that locally adapted thermally tolerant pockets of corals exist at fine-spatial scales within a variety of coral reef systems (Goreau and Macfarlane, 1990;Barshis et al, 2010;Castillo et al, 2012;Kenkel et al, 2013bKenkel et al, , 2015Schoepf et al, 2015).…”
Section: Synthesis Local Adaptation Amidst High Gene Flowmentioning
confidence: 99%